Ocular defect in children with cerebral palsy and its correlation with the types of cerebral palsy - Aumi, Wasim Abed; Afroz, Farhana; Maksud, Shams Ibne; Alam, Mohammad Mahbubul (International Journal of Contemporary Pediatrics, 2021)
Background: Cerebral palsy (CP) describes a group of permanent disorder of the development of movement and posture, causing activity limitation, that are attributed to non-progressive disturbance that occurred in the developing fetal or infant brain. The motor disorders of cerebral palsy are often accompanied by disturbances of sensation, perception, cognition, communication and behavior, by epilepsy, and secondary musculoskeletal problem. However, no known study has been found on this aspect. Objective of this study was to evaluate the ocular defect in children with cerebral palsy and to correlate with the types of CP. Methods: Study was done in the Paediatric Neurology unit of BSMMU from January 2012 to July 2012. One hundred thirty children with cerebral palsy were studied. The patients were randomly selected who full filled the inclusion criteria and ophthalmological examination was done. Results: Sixty four (64%) of CP patients had pathological finding and 36% percent had normal finding. Most of the abnormalities were squint (strabismus) (40%) and refractive error (36.9%). Most of the ocular defects were found in spastic cerebral palsy, mainly in spastic quadriplegia (34.6%) and spastic diplegia (29.2%). Conclusions: Ocular defect like squint and refractive error common associations of cerebral palsy. Spastic quadriplegic and diplegic children had more ocular defects.